Endogenous growth and negative externalities - Stefano Bartolini; Luigi Bonatti (Fondazione Eni Enrico Mattei (FEEM), 1999)
In this paper, the expansion of private production erodes the quality of commonly owned goods, thereby forcing individuals to rely increasingly on private goods to satisfy their needs. In the face of this deterioration, households keep their labour supplies and saving rates relatively high in spite of their increasing private wealth. By so doing, each household contributes to an increase in production and thus has a detrimental–though negligible–impact on commonly owned goods. Perpetual growth is the outcome of this self-fuelling process. Since long-run growth results from a co-ordination failure, it may be higher than socially desirable.
Keywords: O40; Q20; 330; Common property; defensive expenditure; co-ordination failure; undesirable growth; environmental assets; social assets; substitution process; self-fuelling process; Neue Wachstumstheorie; Externer Effekt; Arbeitsangebot; Sparquote; Gemeingüter; Theorie